The Usability of the Preliminary ICF Core Set for Hospitalized Patients After a Hematopoietic Stem Cell Transplantation From the Perspective of Nurses: A Feasibility Study - Stallinga, Hillegonda A.; Bakker, Janita; Haan, Sylvia J.; van Os-Medendorp, Harmieke; Kars, Marijke C.; Overgoor, Louis; Stewart, Roy E.; Roodbol, Petrie F. (Frontiers in Rehabilitation Sciences, 2021)
Background: A hematopoietic stem cell transplantation (HSCT) has a major impact on the functioning and perceived quality of life of patients. To describe the functioning of patients, a preliminary set of 53 categories of the International Classification of Functioning, Disability and Health (ICF) as relevant for HSCT patients has been selected earlier by a Delphi study. For the implementation of this preliminary ICF core set for patients after HSCT in clinical practice, a feasibility study was requested. Methods: A feasibility study was conducted in an explanatory mixed-methods research design. Qualitative data were collected cross-sectionally by semi-structured interviews based on specific topics related to feasibility regarding the use of the preliminary ICF core set for HSCT patients from the perspective of nurses (five in ICF-trained nurses and five regular, untrained, nurses). Quantitative data, were collected longitudinally by using a mobile health application based on ICF in which the ICF trained nurses registered HSCT patients' functioning. Results: Qualitative analysis indicated that using the preliminary ICF core set is practical and acceptable for providing information about the functioning of HSCT patients from the perspective of nurses. In addition, nurses indicated a demand for this information due to its impact on multidisciplinary meetings and clinical decision-making by involving relevant aspects of the functioning of patients. Management support, trained staff, and designated time to focus on functioning are mentioned as requirements for successful implementation. Quantitative analysis demonstrated that the most used 30% (n = 17) ICF categories are included in the preliminary ICF core set for HSCT patients (n = 24). Energy (b130) was the most used ICF category. Family relationships (d760) was the most frequently and highly positively associated ICF category. Conclusions: From the perspective of nurses, the preliminary ICF core set for HSCT patients is feasible and relevant in gaining information regarding functioning. Applying this preliminary ICF core set for HSCT patients in the anamnesis and the nursing consultations contributes to this information. Further research is needed to look at the perspective of other professionals and HSCT patients themselves.